Tar Barreler’s Hump: An Unusual Presentation of a Posttraumatic Pseudolipoma - Babajide Olusola Olubaniyi; Harbir Sidhu; Alex Long; Nigel de-Sousa; Andrew Redfern (Case Reports in Radiology)
This is an interesting paper of a 4 cm posttraumatic pseudolipoma on the back of the neck of an adult man who has participated in “tar barrel rolling” since adolescence. To the best of our knowledge, this is the first case of a pseudolipoma to be reported in the literature in association with tar barreling.